MODEL RESKILLING ADAPTIF UNTUK PENINGKATAN KETERAMPILAN MANAJEMEN BAKAT DI ERA DIGITAL - yusman laia (Faatuatua Media Karya, 2026)
Digital transformation requires organizations to strengthen talent management through adaptive employee skill development. This study develops an adaptive reskilling model to improve talent management competencies based on the needs of digital era capabilities. The data used are sourced from official reports (WEF, OECD, ILO, BPS) as well as pre-post training data at Company X in the technology sector. The research methodology uses a descriptive-analytical approach with the stages of needs analysis, skill gap mapping, reskilling model design, and implementation evaluation. The results show that the adaptive reskilling model can increase digital competency by 38%, productivity by 22%, and managerial readiness in talent management by 31%. This study offers a conceptual model that can be replicated in various organizations seeking to improve talent management amidst technological disruption.